2013
DOI: 10.1603/ec13048
|View full text |Cite
|
Sign up to set email alerts
|

Diel Activity and Behavior of <I>Bagrada hilaris</I> (Hemiptera: Pentatomidae) on Desert Cole Crops

Abstract: Patterns of diel activity and behavior of the Bagrada bug, Bagrada hilaris (Burmeister) (Hemiptera: Pentatomidae), were investigated in a series of field and greenhouse experiments in Yuma, AZ. Adults of B. hilaris were monitored by on-site direct observation on broccoli and cauliflower plants in large-block experimental plots at various intervals throughout consecutive 24-h periods. In the field trials, mean number of B. hilaris adults differed among sampling times, with peak abundance observed consistently b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Although the flight range of Ba. hilaris has not yet been clearly determined, 50 m is greater than the 3-6 m flights commonly observed at peak daytime temperatures for this species (Huang et al 2012). At each site, we placed two potted A. canescens plants 10 m from one another.…”
Section: Bagrada Hilaris Recruitmentmentioning
confidence: 99%
“…Although the flight range of Ba. hilaris has not yet been clearly determined, 50 m is greater than the 3-6 m flights commonly observed at peak daytime temperatures for this species (Huang et al 2012). At each site, we placed two potted A. canescens plants 10 m from one another.…”
Section: Bagrada Hilaris Recruitmentmentioning
confidence: 99%
“…High temperatures influences the walking and mating of bagrada bug (Huang et al, 2013). A study was done in feeding of bagrada bug and results suggested that this pest feeds effectively on brassica crops in the afternoon and evening when temperatures are high (Huang et al, 2013).…”
Section: Major Insect Pests Of Vegetables Grown In South Africamentioning
confidence: 99%
“…Accurately estimating adult density on broccoli can be difficult because adult numbers in fields tend to fluctuate throughout the day. Research has indicated that there is a clear positive association between daily temperature and population density of B. hilaris on broccoli (Huang et al 2013). Those studies consistently showed that adult numbers are very low in the cooler hours of the morning (0600 to 0900 h) and peak in mid to late afternoon (1200 to 1600 h), when temperatures are high.…”
Section: Introductionmentioning
confidence: 96%